PV Systems Installed in Marine Vessels: Technologies and Specifications. (6th March 2013) - Kobougias, Ioannis; Tatakis, Emmanuel; Prousalidis, John
Abstract : Considerations are held about the specificationin whichthe PV plants have to fulfill so that they can be installed on marine vessels. Initially, a brief description of the typical electrical grid of ships is presented, distinguishing the main parts, reporting the typical electrical magnitudes, and choosing the most preferable installation areas. The technical specifications, in whichthe PV plants have to be compatible with, are fully described. They are determined by the special marine environmental conditions, taking into consideration parameters like wind, humidity, shading, corrosion, and limited installation area. The work is carried out with the presentation of the most popular trends in the field of solar cell types and PV system technologies and their ability to keep up with the aforementioned specifications.